التظاهرات السريرية للداء الزلاقي - إبراهيم, علي; زاهر, عزيز; محمد, لؤي (Latakia University Journal -Medical Sciences Series, 2019)
الداء الـزلاقي هو اعتلال معوي متواسط بالمناعة سببه التحسس الدائم للغلوتين في أشخاص ذو نمط وراثي معين. أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم الأطفال خلال عامي (2008-2009) وتضمنت (250) طفلاً وتم تشخيص الداء الزلاقي عند (61) طفلاً منهم وذلك عن طريق الخزعة المعوية عند وجود ضمور زغابي مرحلة ш لمارش ، أو الخزعة المعوية مع أضداد الأندوميزيوم عند وجود ضمور زغابي مرحلةІ أو П لمارش. وقمنا بدراسة المرضى الزلاقيين وكشف التظاهرات السريرية لكل شكل سريري وعلاقتها مع العمر والجنس والحالة الاقتصادية والاجتماعية ، لم نلاحظ وجود اختلافات مهمة بين الجنسين أو بين الفئات العمرية في حدوث الداء الزلاقي. كما لوحظ في دراستنا تشارك واضح بين الشكل ذي التظاهرات المعدية المعوية (الكلاسيكي) والشكل ذو التظاهرات اللامعدية المعوية (اللانموذجي) في شكل سريري هو الشكل ذو التظاهرات المشتركة كان هو الشكل السريري الأشيع 40,98 % يليه الشكل ذو التظاهرات اللامعدية المعوية 31,15 % ثم الشكل ذو التظاهرات المعدية المعوية 21,31 % وأخيراً الشكل اللاعرضي (الصامت) 6,56 %. بالنسبة للشكل السريري اللامعدي المعوي كان فقر الدم بعوز الحديد المعند على العلاج الفموي بمركبات الحديد وقصر القامة هي التظاهرات السريرية الأشيع . Celiac disease is an immune-mediated enteropathy caused by a permanent sensitivity to gluten in genetically susceptible individuals. This study included (250) children and was carried out in the Department of Pediatrics at AL-ASSAD University Hospital in Lattakia during the years (2008-2009); Using intestinal biopsy when there is villous atrophy grade ш (Marsh) or intestinal biopsy with antiendomysial antibodies when there is villous atrophy grade (І,П Marsh), celiac disease was diagnosed in (61) children. We studied celiac patients and detected the clinical manifestations of each clinical pattern and its relation to sex, age, and social economic status. We did not notice important differences between males and females or age groups in the incidence of celiac disease; we noticed in our study a clear correlation between gastrointestinal form (Classical) and non-gastrointestinal form (Atypical) in clinical form, being the form of shared symptoms; it was the most common clinical form (40,98%), non-gastrointestinal form (31,15%), gastrointestinal form (21,31%), and the asystemic form (silent) (6,56%). Concerning the clinical symptoms of non- gastrointestinal form, iron-deficiency anemia resistance to oral iron supplementation and short stature were the most common clinical symptoms.